Commitment to Sustainable Development Goals in marketing communications of ferry companies. - Natalia Wagner; Aleksandra Łapko; Ewa Hącia; Roma Strulak-Wójcikiewicz (PLoS ONE)
Companies are not legally obliged to disclose their commitment to Sustainable Development Goals (SDGs). Despite this, many decide to build their competitive position on the basis of marketing communications about sustainability practices. This paper investigates the landscape of sustainability communications practices within ferry operators in the Baltic Sea Region. The authors have developed an index based on two sources of information: (1) an expert assessment of sustainability categories built on the basis of the SDGs, and (2) an assessment of marketing communications of ferry companies. The results of the study identified three distinct patterns of conduct. An analysis revealed that voyage safety and greenhouse gas emissions are the two categories which the ferry companies are most committed to. The results show that marketing communications on the realisation of social goals gives way to that on commitment to the realisation of environmental goals. Beyond insights into the ferry market, the study presents a valuable methodological tool for assessing sustainability communications across diverse industries.